Molecular Characterization of Complement Component 3 (C3) in the Pearl Oyster Pinctada fucata Improves Our Understanding of the Primitive Complement System in Bivalve - Wang, Zhongliang; Liang, Xueru; Li, Guiying; Liufu, Bai; Lin, Kaiqi; Li, Jinfeng; Wang, Jing; Wang, Bei (Frontiers in Immunology, 2021)
As the central component in the complement system, complement component 3 (C3) plays essential roles in both the innate and adaptive immune responses. Here, a C3 gene (designated as pf-C3) was obtained from the pearl oyster Pinctada fucata by RT-PCR and rapid amplification of cDNA ends (RACE). The pf-C3 cDNA consists of 5634 bp with an open reading frame (ORF) of 5193 bp encoding a protein of 1730 amino acids with a 19 residues signal peptide. The deduced pf-C3 protein possessed the characteristic structure features present in its homologs and contained the A2M_N_2, ANATO, A2M, A2M_comp, A2M_recep, and C345C domains, as well as the C3 convertase cleavage site, thioester motif, and conserved Cys, His, and Glu residues. Phylogenetic analysis revealed that pf-C3 is closely related to the C3s from other molluscs. Pf-C3 mRNA was expressed in all examined tissues including gill, digestive gland, adductor muscle, mantle and foot, while the highest expression was found in digestive gland. Following challenge with Vibrio alginolyticus, pf-C3 expression was significantly induced in hemocytes. Luciferase reporter assays indicated that pf-C3a could activate the NF-κB signal pathway in HEK293T cells. Further knockdown of pf-C3 by specific siRNA could significantly reduce the phagocytosis of V. alginolyticus by hemocytes in vitro. These results would help increase understanding of the function of C3 in the invertebrate immune system and therefore provide new insights into the roles of the primitive complement system in invertebrates.